Impact of genetic polymorphisms of the GnRH gene on productive performance and carcass traits of Japanese Quai - Alshami, Hazim; Ali A. Abdulkareem (University of Thi-Qar Journal of agricultural research, 2025)
This experiment was conducted in the research hall of the College of Agriculture and Marshes at Thi-QarUniversity, and it included two stages: field work and laboratory work. In the field work stage, 200 quail birds were raised from one day old to sexual maturity (end of the field work). At the end of the fifth week of field work, blood samples were collected from the birds after slaughter, and these samples were taken for genetic analysis in the laboratory of the Marshes Research Station/Thi-Qar University. In the laboratory, the genetic material was extracted, and electrophoresis was performed. The amplification product was then sent to the Korean company Microgen to determine the sequence of nitrogenous bases that occupy part of the gene and determine the genotype (genotype) of the gene. The study investigated the effect of the gene on some productive traits, including internal organs (liver, gizzard, heart) and some carcass cuts (wings, thighs, breast, and eviscerated body weight). The results showed that the studied gene could be amplified, and three genetic mutations were identified. The results also showed... Based on the previous results for the three mutations (67.A>G, 323.C>T, and 277.G>C) and the relationship between the genetic structures of the mutations in the GnRH gene with edible viscera, the results showed significant differences for the 277.G>C mutation at a significance level of P≤0.01 in heart and liver weights. The average heart weight for the genetic makeup (GC, 1.836 ± 0.032 A) was the highest average in heart weight, while the genetic makeup (GG, 1.690 ± 0.042 B) was the lowest significant structure. For liver weight, the genetic makeup (GC, 3.775 ± 0.061 A) was the highest average, while the genetic makeup (GG, 3.551 ± 0.061 B) was the lowest significant structure. There was no significant effect of the two mutations (323.C>T and 67.A>G) on the traits The results also showed significant differences for the 277.G>C mutation at a significance level of P≤0.05 in eviscerated body weight, where the average eviscerated body weight for the genetic makeup (GG) was the highest average. The genetic makeup (GG, 105.767 ± 0.853) had the highest average eviscerated body weight, while the genetic makeup (GC, 103.223 ± 0.728) had the lowest average. There were no significant differences between the genetic makeups for the other traits, including breast weight, thigh weight, and wing weight.Additionally, there was no significant effect of the two mutations (323.C>T and 67.A>G) on the mentioned traits In summary, the results showed that: - The 277.G>C mutation had a significant effect on heart weight, liver weight, and eviscerated body weight. - The GG genetic makeup had the highest average eviscerated body weight. There were no significant differences between the genetic makeups for breast weight, thigh weight, and wing weight. The 323.C>T and 67.A>G mutations did not have a significant effect on the mentioned traits.